Immigration policy as public health policy: Trump’s first administration and a critical public health response to the second - Calhoon, Claudia M.; Alang, Sirry M. (Frontiers in Public Health, 2025)
Although President Trump was unable to pass new immigration laws in his first administration, he successfully employed executive orders, rulemaking, and administrative practices that altered significant policies, including benefits programs, immigration enforcement, and criteria for admissibility to the United States. The public health consequences of immigration policies under Trump’s first presidency, deeply punitive immigration policies at the forefront of his 2024 presidential campaign, and far-reaching executive orders that have characterized the early days of his second term present important challenges to practitioners. Arriving at a consensus about how public health institutions respond to political health determinants has become more urgent as increasingly restrictive and punitive immigration policies are proposed and implemented. Critical perspectives that explore the role of power in policy development, implementation, and impact, such as critical race theory, can help public health practitioners do this. We discuss the 45th administration’s immigration policies in terms of colorblindness and race-consciousness, whiteness and entitlement, interest convergence, and the ubiquity of racism. We show how these policies extend dangerously into the current 47th presidency. The impacts of restrictive and punitive immigration policies, as well as the continuous desensitization of the public to extreme approaches, require critical public health responses.